Development and Implementation of the Integrative Toolbox for Headache Management. Issue 4 (9th January 2020) - Beaton‐Starr, Meredith; Rist, Pamela M.; Connor, Julie P.; Wayne, Peter M.; Osypiuk, Kamila; Bernstein, Carolyn
Abstract : Patients with migraine are interested in integrative therapies and overall wellness. They also suffer from social isolation as they try to manage a chronic medical condition. We implemented a three‐part workshop structured as a group visit that teaches multiple integrative therapies from specialists and offers a chance for shared support and learning.